Modo de vida e reprodução camponesa no assentamento Vila Boa em Goiás-GO - Daude, Rodrigo Bastos (2018)
The thesis Modo de vida e Reprodução Camponesa no Assentamento Vila Boa em Goiás-GO has as a study object the culture in the Vila Boa Settlement Project (SP) in the town of Goiás, created on the 6th of September, 1996 where 13 families live. The research subjects were the people settled due to agrarian reform in the SP. We selected the peasant category as a comparative framework to study their culture. This is an investigation movement related to Work, Education and Social Movements of the Graduation Program in Education at the Education College of the Goiás Federal University (PPGE-UFG), which aimed at discussing the following problem: What is the life style of people settled due to agrarian reform of Vila Boa SP, when it comes to constituting survival strategies from a social reproduction perspective? Our purpose was to understand culture in the Vila Boa rural settlement in the town of Goiás - GO, so as to understand drawbacks and advances regarding culture and typical elements of life style of settled people and their social reproduction. We performed a bibliographic study with a qualitative approach, field observation with questionnaires and interviews with the rural settled people in the town of Goiás - GO. The theoretical reference relies on a social background that discusses the agrarian issue, peasantry and agrarian Brazilian politics, as well as the first occupations and rural settlements in Goiás starting at the end of the 1970´s. We also used studies on cultural general theory taking culture as reflection, creation and a set of practices, techniques, symbols and values for social living. Vila Boa SP, as a reflection of such set of practices, has a life style and peasant social reproduction possibilities “forged” in sociability with external agents, neighbors and local public power, atypical in their occupation and constitution as a rural settlement. Thus, settled people´s life styles do not entail a direct influence on peasant social reproduction.